2018
DOI: 10.1155/2018/8795061
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Pyrimidine, Pyrazole, and Pyridine Derivatives and Their Reactivity Descriptors

Abstract: A series of novel pyrimidine (2, 3), pyrazole (4, 5), and pyridine (6) derivatives were synthesized using a chalcone-bearing thiophene nucleus (1). The target compounds were synthesized by reaction of compound (1) with urea, thiourea, malononitrile, hydrazine hydrate, and 2,4-dinitrophenyl hydrazine, respectively. Molecular electronic structures have been modeled within density functional theory framework (DFT). Reactivity indices and electrostatic surface potential maps (ESP maps) allow us to establish trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…For this reason, our focus in this review is on the chemical potential of 3(5)-aminopyrazoles in heterocyclic synthesis. As stated by El-Sattar et al, the chemical potential of a compound reflects the relationship between its structure and reactivity, thus a comparatively higher chemical potential of a compound means a higher reactivity [115]. In compounds that exhibit tautomerism, the reactivity may be controlled by a particular tautomeric form and, according to the Gustafsson paradox, the less abundant tautomer tends to be the most reactive one [116].…”
Section: (5)-aminopyrazole In Heterocyclic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, our focus in this review is on the chemical potential of 3(5)-aminopyrazoles in heterocyclic synthesis. As stated by El-Sattar et al, the chemical potential of a compound reflects the relationship between its structure and reactivity, thus a comparatively higher chemical potential of a compound means a higher reactivity [115]. In compounds that exhibit tautomerism, the reactivity may be controlled by a particular tautomeric form and, according to the Gustafsson paradox, the less abundant tautomer tends to be the most reactive one [116].…”
Section: (5)-aminopyrazole In Heterocyclic Synthesismentioning
confidence: 99%
“…In these circumstances, a paramount need to elucidate the precise chemical potential of the entities present in a specific reactant mixture emerges. HOMO and LUMO states and energies of the tautomeric structures represent the parameters that mostly contribute to their chemical potential; as such, variations alter the acidic/basic and electrophilic/nucleophilic properties of the compounds [85,115]. It was already shown that in heterocycles, including 3(5)-aminopyrazoles, the different characteristics of molecular orbitals promote distinct reactivities of each of the tautomeric species [66,85].…”
Section: (5)-aminopyrazole In Heterocyclic Synthesismentioning
confidence: 99%
“…Density Functional Theory (DFT) was used to determine the equilibrium structure using ab initio levels to support these results. The calculations were performed using the Gaussian 09 package [ 20 ]. Minimum energy-optimized structures for each PFO were obtained by ab initio density functional theory (DFT).…”
Section: Methodsmentioning
confidence: 99%
“…Chalcones transformation might proceed either by 1,4-addition or 1,2-addition. Examples of heterocyclic compounds from chalcones are pyrazoles [1,2], pyrroles [3][4][5], pyrazoline [6], isoxazoles [7][8][9], pyrimidines [10,11], pyridines [12][13][14][15][16], indoles, indazoles, triazoles [17,18], imidazoles [19,20], thiazines [21], 1,5-benzodiazepines, 1,3,4-thiadiazepines, benzoazepines, and 1,5-benzodiazepines [22]. Chalcones are multifunctional molecules that possess promising pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…-b]pyridines 72[15]. While Abd El-Sattar et al reported pyridine 74 from chalcone 73 and malononitrile[16] (Scheme 12).…”
mentioning
confidence: 99%